Estimation of bovine leukemia virus (BLV) proviral load harbored by lymphocyte subpopulations in BLV-infected cattle at the subclinical stage of enzootic bovine leucosis using BLV-CoCoMo-qPCR - Panei, Carlos Javier (2013)
Bovine leukemia virus (BLV) is associated with enzootic bovine leukosis (EBL), which is the most commonneoplastic disease of cattle. BLV infection may remain clinically silent at the aleukemic (AL) stage, cause persistentlymphocytosis (PL), or, more rarely, B cell lymphoma. BLV has been identified in B cells, CD2+Tcells,CD3+Tcells,CD4+Tcells,CD8+Tcells,γ/δT cells, monocytes, and granulocytes in infected cattle that do not have tumors,although the most consistently infected cell is the CD5+B cell. The mechanism by which BLV causes uncontrolledCD5+B cell proliferation is unknown. Recently, we developed a new quantitative real-time polymerase chainreaction (PCR) method, BLV-CoCoMo-qPCR, which enabled us to demonstrate that the proviral load correlates notonly with BLV infection, as assessed by syncytium formation, but also with BLV disease progression. The presentstudy reports the distribution of BLV provirus in peripheral blood mononuclear cell subpopulations isolated fromBLV-infected cows at the subclinical stage of EBL as examined by cell sorting and BLV-CoCoMo-qPCR